Houttuynia cordata Thunb: An Ethnopharmacological Review - Wu, Zhao; Deng, Xinyu; Hu, Qichao; Xiao, Xiaolin; Jiang, Jing; Ma, Xiao; Wu, Mingquan (Frontiers in Pharmacology, 2021)
Houttuynia cordata Thunb (H. cordata), a member of the Saururaceae family, is widely distributed in Asian regions. It plays an important role in traditional health care and disease treatment, as its aboveground stems and leaves have a long medicinal history in China and are used in the treatment of pneumonia and lung abscess. In clinical treatment, it can usually be combined with other drugs to treat dysentery, cold, fever, and mumps; additionally, H. cordata is an edible plant. This review summarizes detailed information on the phytochemistry and pharmacological effects of H. cordata. By searching the keywords ‘H. cordata and lung’, ‘H. cordata and heart’, ‘H. cordata and liver’ and ‘H. cordata and inflammation’ in PubMed, Web of Science and ScienceDirect, we screened out articles with high correlation in the past ten years, sorted out the research contents, disease models and research methods of the articles, and provided a new perspective on the therapeutic effects of H. cordata. A variety of its chemical constituents are characteristic of medicinal plants. By 2019, 220 chemical constituents were isolated from H. cordata, including volatile oils, alkaloids, flavonoids, and phenolic acids. Flavonoids and volatile oils are the main active components. In pharmacological studies, H. cordata showed organ protective activity, such as reducing the release of inflammatory factors to alleviate lung injury. Moreover, H. cordata regulates immunity, enhances the immune barriers of the vagina, oral cavity and intestinal tract, and combined with the antibacterial and antiviral activity of its extract, effectively reduces pathogen infection. Furthermore, experiments in vivo and in vitro showed significant anti-inflammatory activity, and its chemical derivatives exert potential therapeutic activity against rheumatoid arthritis. Anticancer action is also an important pharmacological activity of H. cordata, and studies have shown that H. cordata has a notable effect on lung cancer, liver cancer, colon cancer and breast cancer. This review categorizes the physical activities of H. cordata according to its therapeutic activities in the literature, focuses on multitarget treatment of diseases, and provides insights into the potential drug development of H. cordata.